Youth participation in ethnic and cultural reproduction in the Republic of Kalmykia - Lyudmila V. Namrueva (Novye Issledovaniâ Tuvy, 2015)
Тhe article analyzes the results of a study to learn how the socio-economic transformation of the 2000’s influenced the youth of the Republic, what role do traditional values play in the development of a young person, how young people are involved in the processes of preservation and development of Kalmyk culture.